Reinforcement of columns using different composite materials - Galina E. Okolnikova; Svetlana B. Strashnova; Sikhanyisiwe Mercy Mabhena; Stanislav V. Strashnov (Structural Mechanics of Engineering Constructions and Buildings, 2023)
The adoption in construction of composite materials made by combining two or more materials to produce a material with improved properties over the separate components has been steadily increasing over the past decades. In the past few years there have been advances in composite manufacturing technology, increased demand for sustainable and eco-friendly building materials, and the need for materials that are lightweight and easy for transportation. For these reason, architects and civil engineers incorporate composites into structural elements to achieve these desired goals and optimize the cost of construction. One of the most common composite materials that was introduced to the industry is fiber reinforced polymer (FRP), produced by combining fibers (carbon, glass, or aramid) with a polymer matrix (epoxy or polyester). FRP materials are lightweight, durable and corrosion resistant, which makes them ideal for use in a wide range of construction applications. This study aims to propose a comparison between four different methods as a viable solution to strengthen and reinforce column structures. The structural behavior of three different composite materials was investigated. One traditional concrete-steel column was tested in the experiment for comparison. The other three columns were reinforced using carbon fiber reinforced plastic (CFRP), glass fiber reinforced plastic (GFRP) and stainless steel respectively. The obtained experimental results were analyzed, and comparison of three different systems of reinforcement for strengthening columns with composite materials was performed.